What shapes attitudes on gender roles among adolescents in Bangladesh - Streatfield, Avita J.; Rahman, Md Mahabubur; Khan, Shusmita; Haider, M. Moinuddin; Rahman, Mizanur; Nahar, Quamrun; Jamil, Kanta (Frontiers in Public Health, 2023)
In Bangladesh, large gender differentials exist in outcomes in almost all spheres of life, stemming from conservative norms and attitudes around gender. The aim of the paper is to investigate the extent to which adolescents hold egalitarian attitudes towards gender roles, and to examine the factors that influence egalitarian gender attitudes. The paper uses data from a nationally representative sample survey of 7800 unmarried girls and 5523 unmarried boys ages 15-19 years. Adolescents were considered to have egalitarian attitudes on gender role if they disagreed with all the following four statements, while respondents who agreed with any one of the four statements were considered to have non-egalitarian attitudes: (1) It is important that sons have more education than daughters, (2) Outdoor games are only for boys, (3) Household chores are for women only, even if the woman works outside the home, and (4) Women should not be allowed to work outside the home. Multivariable linear probability regression analysis was implemented to identify the factors shaping attitudes on gender roles. Unmarried girls and boys differ hugely in their views on gender roles regarding socio economic participation-girls were much more egalitarian than boys (58% versus 19%). The multivariate linear probability model results show girls and boys who completed at least grade ten were 31 percentage points (ppt) and 15 ppt more likely to have egalitarian views on gender roles respectively, compared to girls and boys with primary or less education. Adolescents’ individual attitude on gender role is highly associated with the views of their community peers for both girls and boys. Girls and boys who had participated in adolescent programs were 6-7 ppt more likely to have egalitarian attitude than those who were not exposed to these programs. Egalitarian views were also significantly higher, by 5 ppt among girls and 6 ppt among boys, who were members of social organizations compared to those who were not. To create a more egalitarian society, both men and women need to hold progressive attitudes towards gender roles. The interventions must be multilevel, influencing adolescents at the personal, interpersonal, communal, and societal levels.